Novel pyridine-1,3,4-oxadiazole linked 1,2,3-triazole hybrids: synthesis, molecular docking, ADME, DFT study and anti-tumor potential - Aezaz Mathakiya; Bonny Patel; Keval Raval; Jignesh H. Kamdar; Smriti Sharma; Jayesh Dhalani (Results in Chemistry)
Ten novel pyridine-1,3,4-oxadiazole-linked 1,2,3-triazole hybrids (1a-j) were synthesized via a five-step strategy incorporating diverse aromatic substituents with electron-donating and withdrawing groups. Their biological evaluation using the Allium cepa model revealed notable anti-mitotic activity, with compound 1a (chloro-substituted) showing the most pronounced cytotoxic effects by significantly reducing root number and length. Brine shrimp lethality assays supported these results, indicating high toxicity of compound 1a. Molecular docking studies targeting EGFR showed good binding affinity for all compounds (−7.3 to −8.5 kcal/mol), with compound 1a displaying the strongest interaction (−8.5 ± 0.3 kcal/mol). ADME analysis and DFT-based reactivity descriptors further highlighted its drug-likeness and potential for biological interactions. These findings suggest that compound 1a is a promising lead for EGFR-targeted anticancer development and warrants further pharmacological investigation.